PELATIHAN BERSERI TEKNOLOGI INFORMASI DAN KOMUNIKASI DI SEKOLAH DASAR MEKARSARI JAKARTA [A WORKSHOP SERIES OF INFORMATION COMMUNICATION AND TECHNOLOGY AT MEKARSARI ELEMENTARY SCHOOL JAKARTA] - David Agustriawan; Arli Aditya Parikesit; Rizky Nurdiansyah (Universitas Pelita Harapan, 2019)
Industry 4.0 era needs to introduce current information communication and technology (ICT) to the society starting from the elementary school. However, Mekarsari Elementary school does not have the facility nor curriculum to prepare the students to face the era. This corporate social responsibility (CSR) aimed to introduce the kids with the current development of hardware and software. The participants for the series of the workshop are the 15 4th and 5th grade students and two teachers from Mekarsari Elementary school. The intervention was devised by providing user-friendly teaching-learning materials with hands-on activities related to the current development of ICT. The type of study is the “direct philanthropic giving” because it aims at providing knowledge for free. As the result, the students are familiar with: the type of computer’s hardware and software; python programming; budgeting for their daily allowance using Microsoft Excel; and creating a short story and presentation in Microsoft Word and PowerPoint. Based on the survey, the students could comprehend and enthusiastic to complete the hands-on activities. This CSR suggests that each elementary school should have a curriculum and computer laboratory to prepare the youth to compete in industry 4.0 era.